2020
DOI: 10.1590/1982-0275202037e200066
|View full text |Cite
|
Sign up to set email alerts
|

Impactos psicológicos e ocupacionais das sucessivas ondas recentes de pandemias em profissionais da saúde: revisão integrativa e lições aprendidas

Abstract: Resumo Sucessivas ondas de pandemias podem impactar a saúde mental dos profissionais da saúde. Nesse sentido, este estudo objetivou apresentar evidências científicas sobre fatores associados ao impacto ocupacional e psicológico provocado por elas sobre os profissionais da saúde. Após realizada uma revisão integrativa da literatura com buscas em cinco bases de dados, nove artigos foram incluídos neste estudo. O principal impacto explorado nos artigos é que as situações de pandemias guardam relação com quadros d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
56

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 17 publications
0
34
0
56
Order By: Relevance
“…In addition, during the pandemic, there has been a documented increase in the risk of development of symptoms of anxiety, depression, and other psychological problems. This is due to the increasing stress from the characteristics of the pandemic itself, the decrease in mobility, the economic slowdown, and closing of schools, which are widely adopted measures to control transmission of the novel coronavirus and prevent health systems' collapse 5 . In this scenario, people tend to become more anxious and depressed and may adopt extreme health risk behaviors such as suicidal ideation or suicide attempts and self-mutilation 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, during the pandemic, there has been a documented increase in the risk of development of symptoms of anxiety, depression, and other psychological problems. This is due to the increasing stress from the characteristics of the pandemic itself, the decrease in mobility, the economic slowdown, and closing of schools, which are widely adopted measures to control transmission of the novel coronavirus and prevent health systems' collapse 5 . In this scenario, people tend to become more anxious and depressed and may adopt extreme health risk behaviors such as suicidal ideation or suicide attempts and self-mutilation 23 .…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19, the disease caused by SARS-CoV-2 and that emerged in late 2019 in Wuhan, China, was declared by the World Health Organization (WHO) as the sixth public health emergency that required attention as a pandemic 4 . The health measures to control transmission and guarantee the population's protection, flatten the transmission curve, and prevent the health services' collapse altered people's daily lives 5,6 . Specifically, according to the WHO, the closing of teaching institutions as a measure to contain COVID-19 cases removed 1.5 billion children and adolescents from schools 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The authors identified that the risk factors for psychological distress include the following: being younger, inexperienced, parents to dependent children and quarantined, having an infected family member, lacking practical support, and stigma. Strategies that may be easily employed to minimize the psychological distress of health professionals are as follows: clear communication, access to adequate individual protection, sufficient rest, and practical and psychological support; such strategies are associated with mortality reduction 13 .…”
mentioning
confidence: 99%
“…4 These measures also changed the routine and the way of organizing life. [5][6] At the forefront of coping are health professionals, especially the Nursing team. In addition to the demands of the services, these professionals face the objective issues of their lives, their families, their children, and the need to reorganize the routine to serve the population and avoid further chaos in the services.…”
Section: Introductionmentioning
confidence: 99%
“…Being at the forefront of coping with COVID-19 heightens concerns and fears, with an emphasis on the fear of being infected and, therefore, infecting their family members, especially their children. 5 Although it is claimed that children are not a risk group for infection or worsening of the disease, little is known about the evolution of the disease in this population. 9 Furthermore, the impact on children's mental health is highlighted, as they are sensitive observers and react to the stresses experienced by their parents, family and community.…”
Section: Introductionmentioning
confidence: 99%